The material subject
1 online resource (xxi, 224 pages)
Keywords: "This volume emphasizes the role of bodily and material culture in making subjects, with a focus on empirical field research and theoretical sophistication. In particular, the work is situated in the anthropological study of techniques, materiality and power via the ideas of the Matière à Penser (MaP) school of thought. It provides students and scholars of material culture with valuable access to an intellectual tradition developed mostly in France and to emerging cross-disciplinary research. The book highlights the embodied subject as a holistic entity - including mind, drives and pains - engaged in relationships with others, and in doing so rejects the Western notion of the self-managing individual with disembodied thought. The chapters mediate different scales of engagement through a focus on practices and connect the study of physical properties (of both humans and objects) and gestures to larger questions of how individuals are connected with their environment and each other through actions"--